2000
DOI: 10.1002/(sici)1097-4636(2000)53:2<143::aid-jbm3>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fabrication method and resin type on performance of tibial bearings

Abstract: Polyethylene has been used successfully for more than 30 years as an orthopedic bearing material. During this time, several polyethylene resins and fabrication methods have been used to produce bearings. Some bearings fail prematurely due to fatigue, which has been linked to oxidation and degradation of mechanical properties resulting from gamma sterilization in air. Fabrication method and/or resin have been hypothesized to govern whether oxidative degradation occurs in gamma-sterilized bearings. This study ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 7 publications
0
25
0
1
Order By: Relevance
“…Previous studies have thus reported both lower oxidation levels and superior damage resistance of polyethylene components molded from 1900H resins as compared with those machined from GUR 415 extruded bars [3740]. 1900H polyethylene, however, was demonstrated to lose mechanical strength at lower oxidation levels than GUR 415 polyethylene, so the apparent advantage of the former material might be lost as it oxidizes [38]. Recently, no significant difference in the in vitro wear performance was observed between conventional polyethylene components and unirradiated specimens manufactured from various resins and conversion techniques, including 1900H and direct compression molding [4142].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have thus reported both lower oxidation levels and superior damage resistance of polyethylene components molded from 1900H resins as compared with those machined from GUR 415 extruded bars [3740]. 1900H polyethylene, however, was demonstrated to lose mechanical strength at lower oxidation levels than GUR 415 polyethylene, so the apparent advantage of the former material might be lost as it oxidizes [38]. Recently, no significant difference in the in vitro wear performance was observed between conventional polyethylene components and unirradiated specimens manufactured from various resins and conversion techniques, including 1900H and direct compression molding [4142].…”
Section: Discussionmentioning
confidence: 99%
“…From our results, DCM inserts demonstrated less backside wear than non-DCM inserts independent of time in vivo. In several studies, compression-molded polyethylene components have exhibited better articular-sided wear characteristics than machined components, indicating compression-molded polyethylene is better suited for clinical applications [2,12,24,35,38]. The sterilization process has also improved since Bohl et al demonstrated gamma irradiation in an oxygen environment resulted in poor wear characteristics [3].…”
Section: Discussionmentioning
confidence: 99%
“…Compression-molded inserts are fabricated by directly conforming polyethylene resin to molds of predetermined geometry. Although earlier reports indicated compression-molded inserts had better articularsided wear characteristics than machined components, limited data are available characterizing the impact of manufacturing technique on backside polyethylene wear [12,35,38]. An improved understanding of the relationship between polyethylene manufacturing and backside wear may facilitate improvements in polyethylene bearing design and development, which would improve implant survival and functional outcomes for patients with TKAs.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the late 1990s, the benefits of modular MBT components were questioned by reports of backside wear of the polyethylene modular insert, poorly functioning tibial base plate locking mechanisms, and osteolysis associated with these problems [4,8,24,27]. Alternatives to MBT components were therefore developed.…”
Section: Introductionmentioning
confidence: 99%